2007
DOI: 10.1143/jpsjs.76sa.190
|View full text |Cite
|
Sign up to set email alerts
|

Structural Analysis of Iron Mixed-Valence Complex (n-C3H7)4N[FeIIFeIII(dto)3] (dto = C2O2S2) under High Pressure

Abstract: Iron mixed-valence complex, (n-C 3 H 7 )4N[Fe II Fe III (dto) 3 ] shows an electron-transfer between Fe(II) and Fe(III) ion accompanied by a spin transition, i.e. a charge-transfer (CT) phase transition at 122.4 K. The pressure dependence of CT phase transition is evaluated by a x-ray structural analysis under high pressure. We report the structural changes of the CT transition under high pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…However, the CTPT behavior of 1 did not change and increased with increasing pressure, although 2 showed a high CTPT temperature with increasing pressure. This indicates the occurrence of a structural phase transition triggered by the high pressure, not a continuous structural change under the applied pressures of 2 . , We focused on the layer-by-layer stacking manner to elucidate the structural phase transition. When the pressure was applied, the crystal structure of 1 changed from an eclipsed stacking manner to a staggered form, which was a metastable state.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the CTPT behavior of 1 did not change and increased with increasing pressure, although 2 showed a high CTPT temperature with increasing pressure. This indicates the occurrence of a structural phase transition triggered by the high pressure, not a continuous structural change under the applied pressures of 2 . , We focused on the layer-by-layer stacking manner to elucidate the structural phase transition. When the pressure was applied, the crystal structure of 1 changed from an eclipsed stacking manner to a staggered form, which was a metastable state.…”
Section: Resultsmentioning
confidence: 99%
“…It is possible to increase the phase transition temperature when Δ S trs is small or Δ H trs is large. Itoi and Kojima reported that the CTPT temperature of 2 shifted to a high value with an increase in pressure, as confirmed by variable-pressure magnetic measurements and a powder X-ray diffraction (PXRD) analysis . This suggests the contribution of a pressure-induced structural change to the increase in Δ H .…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the former approach was applied for 1 and it was found that T CTPT increased up to approximately 200 K with an increase of external pressure from 10 −4 to 0.9 GPa. 15,16 On the other hand, chemical modification allows the control of internal pressure, and it is well known as "chemical pressure" in spin-crossover (SCO) studies. 17 Recently, we reported the structural and magnetic studies of (Ph 4 P)[Fe II Fe III (dto) 3 ] (2; Ph 4 P = tetraphenylphosphonium).…”
Section: Introductionmentioning
confidence: 99%